Linear alkanes as a tool to evaluate intraspecific differences in social wasps - Michelutti, Kamylla Balbuena; Cardoso, Claudia Andrea Lima; Antonialli-Junior, William Fernando (Ciência e Natura, 2018)
Cuticular hydrocarbons are found in the epicuticle of insects and act during interactions between nestmates in social insects. Among the classes of these compounds, branched alkanes stand out acting as flags during intracolonial interactions, therefore, varying significantly intraspecificaly. However, there is evidence that linear alkanes can also act as signals in these interactions and therefore would also be important to assess intraspecific differences in colonies of social insects. Thus, the hypothesis of this study is that linear alkanes can be used as a tool to establish intraspecific relationships in a species of social wasp. Linear alkanes of all developmental stages were evaluated from colonies of the species Mischocyttarus consimilis Zikán (Hymenoptera, Vespidae). 21 linear alkanes were detected, with the majority ranging from n-C26 to n-C33. There is significant variation between the compounds of all developmental stages, both from samples of different colonies and populations. Therefore, the results validate the hypothesis that variation in composition of linear alkanes can be useful to assess intraspecific differences in social wasps.